EFFECT OF HORMONAL AND HERBAL THERAPIES ON POSTPARTUM PLASMA PROFILE OF GLUCOSE AND TOTAL PROTEIN IN HOLSTEIN FRIESIAN COWS - PATEL, B B; PATEL, D M; PATEL, J A (The Indian Journal of Animal Reproduction, 2023)
Twenty-eight freshly calved HF cows of University farm were monitored through clinical diagnosis andfortnightly plasma profile of glucose and total protein from the day of calving till 75 days postpartum. Bloodglucose and protein status was also studied at 6 and 24 h postpartum in all the animals. The animals wererandomly and equally divided into four groups, each of seven animals. Group I served as Control; GroupII included PGF2,: 500 μg (lliren) i/m alone and Group Ill PGF2r: 500 μg (lliren) plus Oxytocin 50 units i/mimmediately after parturition, while Group IV was treated with intra-uterine infusion of herbal ecbolic (Vantab)at weekly interval thrice. The regression of pregnancy CL, uterine involution, first and fertile estrus postpartumwere significantly earlier/shorter in PG treated than the herbal treated and control group. The overall meanplasma glucose and total protein concentrations were 57.79 0 0.50 (range 50 to 67) mg/di and 7.25 0 0.05(range 6.65 to 7.87) g/dl, respectively. The differences between groups were highly significant (P
Keywords: Holstein Friesian cows; Hormone therapy; Plasma glucose; Plasma protein; Postpartum period